Hubungan Self-Compassion terhadap Kemampuan Menerima Kritik Akademik pada Mahasiswa di Jabodetabek - Madeline Gaby Sie; Niken Widi Astuti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine the relationship between self-compassion and the ability to accept academic criticism among undergraduate students in the Jabodetabek region. A correlational quantitative approach was employed involving 421 active S1 students selected through purposive sampling. Self compassion was measured using the SelfCompassion Scale (SCS) by Neff (2023), while the ability to accept academic criticis m was assessed with the Feedback Orientation Scale (FOS) by Linderbaum & Levy (2010). Data analysis using Spearman’s Rho revealed a weak negative correlation). These findings indicate that higher levels of self compassion are associated with a slightly lower orientation toward actively seeking and valuing academic feedback. The results suggest that students with very high self compassion have achieved strong self acceptance, reducing their perceived need for external validation through criticism. This study recommends that self compassion enhancement programs in universities be integrated with training on actively seeking and utilizing constructive academic feedback.